Crosslinked polymalic acid shape deformation material with thermo-photoelectric response and preparation method of cross-linked polymalic acid shape deformation material

CN119390986AInactive Publication Date: 2025-02-07YANGZHOU UNIV

Patent Information

Application Number
CN202411752122.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing crosslinked polymalic acid shape deformation materials can only respond to one or two external stimuli, and cannot achieve the ability to respond to multiple external stimuli at the same time.

Method used

By introducing polycaprolactone diol and nanocarbon fibers, a crosslinked polymalic acid shape deformation material with thermal photoelectric response is prepared, so that it has a shape deformation response to heat, electricity, sunlight and near-infrared lasers and is crystallized The melting temperature is easy to regulate.

Benefits of technology

The material has the ability to respond to various external stimuli (thermal, electricity, sunlight, near-infrared laser) at the same time, and meets different engineering needs by regulating the crystallization melting temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390986A_ABST
    Figure CN119390986A_ABST
Patent Text Reader

Abstract

The invention relates to a cross-linked polymalic acid shape deformation material with thermo-photoelectric response and a preparation method thereof in the field of polymer composite materials, and during preparation, polymalic acid, polycaprolactone glycol and carbon nanofibers are fully mixed in a solvent tetrahydrofuran according to the weight ratio of 64%-66%, 32%-33% and 1%-4%; pouring the mixture into a mold, heating to 100-160 DEG C under a vacuum condition, and reacting for 20-40 minutes; carrying out esterification reaction on the polymalic acid and the polycaprolactone glycol; and further preserving heat and curing for 12-36 hours in the inert atmosphere, cooling and taking out after the curing is finished, thereby obtaining the target product, namely the cross-linked polymalic acid shape deformation material. The material has shape deformation response to heat, electricity, sunlight and near-infrared laser, and the crystallization melting temperature is easy to regulate and control. The obtained material can be used as a joint material of a robot.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polymer composite material, in particular to a shape-deformable material with multiple response conditions. Background Art

[0002] In the prior art, the cross-linked polymalic acid shape-deforming material is a material that can spontaneously and actively deform under the influence of the external environment. The cross-linked polymalic acid shape-deforming material can realize the conversion of external stimuli into mechanical energy, and has the characteristics of biocompatibility, biodegradability, non-contact, and easy control. Generally, the cross-linked polymalic acid shape-deforming material can trigger shape changes in thermal stimulation. Chinese patent ZL202110395571.X discloses a biodegradable asynchronously responsive polymalic acid active deformation material that can undergo shape deformation in thermal stimulation. Chinese patent ZL202010147393.4 discloses a shape-deforming material that can quickly and visually identify the concentration of mixed organic solvents and its use, which can undergo shape deformation in solvent stimulation. ZL201810935286.0 discloses a mechanical response degradable material with adjustable shape deformation temperature, which can regulate the temperature threshold for shape deformation in thermal stimulation through the chain length of the diol cross-linking agent.

[0003] The disadvantage is that the current cross-linked polymalic acid shape-deforming materials can only respond to one or two external stimuli and cause spontaneous active deformation, and it is impossible to achieve the ability of a material to respond to multiple external stimuli at the same time. Summary of the invention

[0004] The purpose of the present invention is to provide a cross-linked polymalic acid shape-deforming material having thermophotoelectric response and the like, so that it has shape-deforming response to heat, electricity, sunlight and near-infrared laser, and at the same time, its crystallization melting temperature is easy to control.

[0005] In order to solve the above technical problems, the technical solution of the present invention is: a method for preparing a cross-linked polymalic acid shape-deforming material having both thermophotoelectric response, comprising the following steps:

[0006] S1, polymalic acid (PMA), polycaprolactone diol (PCL diol) and nanocarbon fiber (CNF) are fully mixed in a solvent of tetrahydrofuran (THF) at a weight ratio of 64% to 66%, 32% to 33%, and 1% to 4%, and the amount of tetrahydrofuran is 3 to 10 times the total weight of polymalic acid, polycaprolactone diol and nanocarbon fiber;

[0007] S2, pouring the mixture obtained in step S1 into a mold, heating it to 100-160°C under vacuum conditions, and reacting it for 20-40 minutes; polymalic acid and polycaprolactone diol undergo esterification reaction, and continuously vacuumizing during the reaction process, the solvent tetrahydrofuran evaporates completely under vacuum and heating conditions, and the nano-carbon fibers are evenly dispersed in the reaction product;

[0008] S3, continue to further heat preservation and curing in an inert atmosphere for 12h to 36h, cool down and take out after completion, and obtain the target product cross-linked polymalic acid shape-deforming material.

[0009] Furthermore, the molecular weight of the polymalic acid is 1500±50 g / mol, and the molecular weight of the polycaprolactone diol is 4000-10000 g / mol.

[0010] The inert atmosphere is argon, helium or nitrogen atmosphere.

[0011] The present invention uses polymalic acid as a cross-linking agent, introduces crystallizable polycaprolactone diol to construct a cross-linked PMA network, so that the material has a customizable crystallization melting temperature, that is, a shape deformation trigger temperature, and the crystallization melting temperature can be regulated according to the needs of the actual engineering situation. On this basis, nano-carbon fiber is used as a functional filler, and the conversion capabilities of sunlight / heat, near-infrared laser / heat, and electricity / heat of nano-carbon fiber are utilized to prepare a cross-linked polymalic acid shape deformation material induced by heat, electricity, sunlight, and near-infrared laser. The material can be used to make the driving parts of the robot, and the cross-linked PMA with different network densities is used as different joint materials. By connecting the metal arm, a robot arm that can perform precise movements can be prepared. Under the stimulation of external heat, electricity, sunlight, and near-infrared laser, different joints make different shape recovery responses, which provides a new technical idea for the development of robots. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 Schematic diagram of the deformation mechanism of cross-linked polymalic acid shape-deformable material.

[0013] Figure 2 is the molecular weight of PCL diol and T of PMACL sample m relationship diagram.

[0014] Figure 3 The sample was placed under a xenon lamp (one sun, 1kWm -2 )’s shape deformation process diagram.

[0015] Figure 4 This is a graph of the shape deformation rate of samples with different CNF contents under sunlight.

[0016] Figure 5 NIR light-induced shape deformation of the sample.

[0017] Figure 6 The shape deformation velocity diagram of samples with different CNF contents under near-infrared laser irradiation.

[0018] Figure 7 is the thermally induced shape deformation of the sample.

[0019] Figure 8 The electrically induced shape deformation process of the sample: (a) twisted spline, (b) stretched spline.

[0020] Fig. 9 The shape deformation rate diagram of samples with different CNF contents under electrical stimulation. DETAILED DESCRIPTION

[0021] Embodiment 1:

[0022] First, PMA (molecular weight of 1500g / mol), PCL diol (molecular weight of 10000g / mol) and CNF were added to 5 times of their weight and THF at a mass ratio of 32.5%, 65% and 2.5% and stirred vigorously. Then the stirred mixture was poured into a polytetrafluoroethylene (PTFE) mold. Then, it was reacted at 130°C for 30min under vacuum conditions, and finally, it was further heat-cured in an argon inert atmosphere for 24h and then cooled to room temperature to obtain the target product, cross-linked polymalic acid shape-deforming material.

[0023] Embodiment 2-3, comparative example 1-2:

[0024] The same process as in Example 1 was used, only the reaction temperature was changed, as shown in Table 1.

[0025] Table 1 Mechanical properties of samples at different reaction temperatures

[0026] Reaction temperature (℃) Yield strength(MPa) Example 2 100 20 Example 1 130 30 Example 3 160 23 Comparative Example 1 80 Material is not formed Comparative Example 2 200 Too high temperature, material degradation

[0027] As can be seen from Table 1, a reaction temperature below 100°C will result in the material being shapeless and unusable, a reaction temperature above 160°C will result in material degradation, and a reaction temperature within the range of 100°C to 160°C will have good mechanical properties.

[0028] Embodiment 4-5, comparative example 3-4:

[0029] The same steps as in Example 1 were used, only the reaction time was changed, as shown in Table 2.

[0030] Table 2 Mechanical properties of samples with different reaction times

[0031] Reaction time (min) Yield strength(MPa) Example 4 20 15 Example 1 30 30 Example 5 40 30 Comparative Example 3 10 The reaction time is too short and the material is not formed. Comparative Example 4 50 No change in yield strength

[0032] As can be seen from Table 2, a reaction time lower than 20 min will result in incomplete reaction and unformed material. A reaction time higher than 30 min will result in no increase in yield strength, wasting energy. Good mechanical properties can be achieved within the reaction time range of 20 min to 40 min.

[0033] Embodiment 6-7, comparative example 5-6:

[0034] The same steps as in Example 1 were used, only the curing time in the inert gas was changed, as shown in Table 3.

[0035] Table 3 Mechanical properties of samples with different curing times in inert gas

[0036]

[0037]

[0038] As can be seen from Table 3, a curing time of less than 12 h will result in incomplete curing and unformed materials. A curing time of more than 36 h will result in no increase in yield strength, wasting energy. In an inert gas, the curing time ranges from 12 h to 36 h and has good mechanical properties.

[0039] Embodiment 8-9, comparative example 7-8:

[0040] The same steps as in Example 1 were used, only the weight percentage of the carbon nanofibers was changed, as shown in Table 4.

[0041] Table 4 Yield strength and elongation at break of samples with different mass ratios

[0042]

[0043] It can be seen from Table 4 that when the mass ratio is 30:60:10, the material is not formed, and when the mass ratio is 33.3:66.6:0, the yield strength is too low and the material cannot be used. When PMA, PCL diol and CNF are between 32-33%, 64-66%, and 1-3%, the samples all have high yield strength and can also give the system the ability of electrothermal and photothermal conversion, but as the weight percentage of nanocarbon fibers increases, the sample's and elongation at break also decrease. The appropriate weight percentage of carbon nanofibers can be selected according to actual needs.

[0044] Embodiment 10-11, comparative example 9-10:

[0045] The same steps as in Example 1 were used, except that the molecular weight of PCL diol was changed, as shown in Table 5.

[0046] Table 5 Elongation at break of samples with different PCL diol molecular weights

[0047]

[0048]

[0049] It can be seen from Table 5 that the elongation at break of the samples shows an increasing trend with the increase of PCL molecular weight, among which the strain level of PMACL-10k sample at 75°C ambient temperature exceeds 2000%, and the yield strength of PMACL-10k sample is also the highest among the series of samples. Whether at room temperature or at high temperature, the mechanical strength and tensile ductility of PMACL-10k sample are the best among all samples, so PMACL-10k sample can be selected as the optimized sample to prepare nanocomposites.

[0050] Table 6 Deformation speed of samples induced by sunlight at different mass ratios

[0051] Quality Ratio Sample deformation speed (deg / s) Example 8 33:66:1 0.6 Example 1 32.5:65:2.5 0.8 Example 9 32:64:4 1.0 Comparative Example 7 33.3:66.6:0 No sunlight-induced deformation capability Comparative Example 8 30:60:10 The material is not formed and cannot be used

[0052] It can be seen from Table 6 that if the weight percentage of nano-carbon fibers is too high (>10wt%), the material will be shapeless and unusable, and if the weight percentage is too low (<1wt%), the material will not have the ability to respond to sunlight. When the weight percentage of nano-carbon fibers is in the range of 1 to 4wt%, the material has the ability to induced shape deformation by sunlight, and the deformation speed of the material increases with the weight percentage of nano-carbon fibers.

[0053] Table 7 Deformation speed of samples induced by near-infrared laser at different mass ratios

[0054]

[0055]

[0056] As can be seen from Table 7, if the weight percentage of nano carbon fiber is too high (>10wt%), the material will not be formed and cannot be used normally, and if the weight percentage is too low (<1wt%), the material will not have the ability to respond electrically. When the weight percentage of nano carbon fiber is in the range of 1-4wt%, the material has the ability to be induced by near-infrared laser shape deformation, and the deformation speed of the material increases with the weight percentage of nano carbon fiber.

[0057] Table 8 Deformation speed of samples induced by electrical stimulation at different mass ratios

[0058] Quality Ratio Sample deformation speed (deg / s) Example 8 33:66:1 15 Example 1 32.5:65:2.5 15.5 Example 9 32:64:4 16 Comparative Example 7 33.3:66.6:0 No electrical response capability Comparative Example 8 30:60:10 The electric heating effect is too strong, causing spontaneous combustion

[0059] As can be seen from Table 8, if the weight percentage of nano carbon fiber is too high (>10wt%), the material will not be formed and cannot be used, and if the weight percentage is too low (<1wt%), the material will not have the ability to respond electrically. When the weight percentage of nano carbon fiber is within the range of 1-4wt%, the material has the ability to electrically induce shape deformation, and the deformation speed of the material increases with the weight percentage of nano carbon fiber.

[0060] Embodiment 1, comparative example 11-14:

[0061] The same steps as in Example 1 were used, only the type of diol was changed, as shown in Table 9.

[0062] Table 9 Elongation at break of different diol samples

[0063] Types of different diol samples Elongation at break of sample (%) Example 1 Polycaprolactone diol 2000 Comparative Example 11 Hexanediol 7.16 Comparative Example 12 Caprylyl glycol 7.69 Comparative Example 13 Decanediol 8.73 Comparative Example 14 Dodecanediol 11.15

[0064] It can be seen from Table 9 that the elongation at break of different diol samples is different, among which the strain level of the polycaprolactone diol sample at 75°C ambient temperature exceeds 2000%, and the yield strength of the polycaprolactone diol sample is far higher than that of the same series of samples. Whether in room temperature or in high temperature environment, the mechanical strength and tensile ductility of the polycaprolactone diol sample are the best among all samples, so the polycaprolactone diol sample is selected as the optimized sample to prepare the nanocomposite material.

[0065] To summarize, for the materials mentioned in this patent, the best reaction temperature is in the range of 100°C to 160°C, the best reaction time is in the range of 20min to 40min, the best curing time in an inert gas is in the range of 12h to 36h, the molecular weight of the PCL diol used is in the range of 4000 to 10000g / mol, and the weight percentage of the added nano-carbon fibers is in the range of 1wt% to 4wt%. Reasonable selection should be made according to the actual product usage scenario.

[0066] Its beneficial effects are:

[0067] 1. Customizable crystallization melting temperature ( Figure 2 ): T of PMACL sample m With the increase of the molecular weight of PCL diol involved in cross-linking, the T of PMACL samples prepared by controlling the molecular weight of PCL diol in the range of 1k to 10k (g / mol) m It can be adjusted within the range of 36.4℃~56.7℃.

[0068] 2. Shape deformation induced by sunlight ( Figure 3): The curled sample is placed under the irradiation of standard sunlight. After about 300 seconds of irradiation, the "curled" sample is completely opened and restored to the original straight strip shape. And the samples with different CNF contents have different heating rates under sunlight irradiation. With the increase of CNF content, the solar-heat conversion rate of PMACL-CNFx sample (where x is the weight percentage of filled CNF) also increases. Samples with higher CNF content have higher solar-heat conversion efficiency. The sample is first bent into a U shape, and then deformed into a straight strip under the stimulation of sunlight. The deformation speed is expressed as angle / time ( Figure 4 ).

[0069] 3.Near-infrared laser-induced shape deformation ( Figure 5 ): When the bent sample is irradiated with an infrared laser, the bent strip can automatically return to a straight shape. After the near-infrared laser irradiates the sample for 10 seconds, the sample temperature rises to between 55°C and 75°C (the temperature of samples with different CNF contents is different), and the bent sample is completely deformed into a straight strip. After irradiating the sample for 25 seconds, the temperature can rise to 80°C at most. The sample is first bent into a U shape, and then deformed into a straight strip under the stimulation of the near-infrared laser. The deformation speed is expressed as angle / time ( Figure 6 ).

[0070] 4. Shape deformation induced by thermal stimulation ( Figure 7 ): The stretched sample is placed in a hot environment and deformed to its original shape. Both PMACL-CNFx and PMACL samples can exhibit excellent shape deformation capabilities.

[0071] 5. Shape deformation induced by electrical stimulation ( Figure 8 ): The sample is twisted or stretched to a temporary shape, and a voltage is applied at both ends to restore it to its original shape. The conductivity of the PMACL-CNFx sample increases with the increase of CNF content. Under the stimulation of voltage, it takes only 10 seconds to restore to its original shape. The sample is first bent into a U shape, and under the stimulation of near-infrared laser, it is restored to a straight strip shape. The deformation speed is expressed as angle / time ( Fig. 9 ).

[0072] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.

Claims

1. A method for preparing a cross-linked polymalic acid shape-deforming material having both thermophotoelectric response, characterized in that: The steps include: S1, polymalic acid, polycaprolactone diol and nano-carbon fiber are fully mixed in a solvent of tetrahydrofuran at a weight ratio of 64% to 66%, 32% to 33% and 1% to 4%, and the amount of tetrahydrofuran is 3 to 10 times the total weight of polymalic acid, polycaprolactone diol and nano-carbon fiber; S2, pouring the mixture obtained in step S1 into a mold, heating it to 100-160°C under vacuum conditions, and reacting it for 20-40 minutes; polymalic acid and polycaprolactone diol undergo esterification reaction, and vacuum is continuously drawn during the reaction process, and the solvent tetrahydrofuran evaporates completely under vacuum and heating conditions, and the nano-carbon fibers are uniformly dispersed in the reaction product; S3. Continue to further heat-preserve and cure in an inert atmosphere for 12 h to 36 h, cool down and take out after completion, and obtain the target product, a cross-linked polymalic acid shape-deforming material.

2. The method for preparing a cross-linked polymalic acid shape-deforming material having a thermophotoelectric response according to claim 1, characterized in that: The molecular weight of the polymalic acid is 1500±50 g / mol, and the molecular weight of the polycaprolactone diol is 4000-10000 g / mol.

3. The method for preparing a cross-linked polymalic acid shape-deforming material having a thermophotoelectric response according to claim 1, characterized in that: The inert atmosphere is argon, helium or nitrogen.

4. A cross-linked polymalic acid shape-deforming material having both thermophotoelectric response, characterized in that: Prepared according to the method according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Shape memory temperature-adjustable mechanical-response degradable material

    CN109320695A

  • Shape memory material capable of quickly and visually identifying concentration of mixed organic solvent and application thereof

    CN111234272A

  • Biodegradable asynchronous response polymalic acid active deformation material

    CN113278154A

Cited By

  • Ultraviolet-controlled photo-reversible dynamic crosslinking high polymer material with reversible antibacterial, shape deformation and toughening functions as well as preparation method and application of photo-reversible dynamic crosslinking high polymer material

    CN122037242A